1977
DOI: 10.1172/jci108859
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Low Immunoreactive Human Plasma Dopamine-β-Hydroxylase

Abstract: A B S T R A C T (IDBH) in blood from a randomly selected population of adolescents was 824±38 ng/ml (mean±SEM, n = 134). The correlation coefficient of enzymatic DBH with IDBH for this group of 134 adolescents was 0.84 (P < 0.001). Ofthese subjects, 3.7% had values of <100 ng/ml and appeared to compose a separate subgroup analogous to the 3-4% of the population that is homozygous for the allele for low enzymatic activity. There was a significant siblingsibling correlation of IDBH values in the 14 sibling pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Early studies conceptualizing plasma DBH activity as a qualitative trait suggested that a major gene polymorphism accounted for a large proportion of the variance in activity of this enzyme in the normal human population [Weinshilboum et al, 1975;Dunnette and Weinshilboum, 1977;Weinshilboum, 19791. Other investigators, using complex segregation analysis and linkage analysis to analyze DBH activity as a quantitative trait, found evidence that a major gene contributed to the regulation of the activity of this enzyme in the blood [Elston et al, 1979;Goldin et al, 1982;Asamoah et al, 1987;Wilson et al, 19881 and that a polygenic component was also involved in the genetic transmission of DBH activity [Goldin, 19851.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies conceptualizing plasma DBH activity as a qualitative trait suggested that a major gene polymorphism accounted for a large proportion of the variance in activity of this enzyme in the normal human population [Weinshilboum et al, 1975;Dunnette and Weinshilboum, 1977;Weinshilboum, 19791. Other investigators, using complex segregation analysis and linkage analysis to analyze DBH activity as a quantitative trait, found evidence that a major gene contributed to the regulation of the activity of this enzyme in the blood [Elston et al, 1979;Goldin et al, 1982;Asamoah et al, 1987;Wilson et al, 19881 and that a polygenic component was also involved in the genetic transmission of DBH activity [Goldin, 19851.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with dopamine ␤-hydroxylase deficiency, activity of this enzyme is absent in plasma; however, there is genetically determined interindividual variation in plasma dopamine ␤-hydroxylase, with 3% to 4% of the normal adult population having near-zero concentrations (38 ). The disorder can be confirmed by the evaluation of the norepinephrine-to-dopamine ratio in plasma.…”
Section: Secondary Abnormalities Of Serotonin and Catecholaminesmentioning
confidence: 99%
“…5 Serum DBH activity of human as well as gorilla have been known to be polymorphic for the last 30 years. [6][7][8][9] This inter-individual difference in serum DBH of European population has been stated as being mostly related to a promoter polymorphism at the À1021 promoter region (C to T, rs1611115). 10 Furthermore, there are probably a few pathogenetic germline mutations of DBH that explain rare congenital deficiency.…”
Section: Introductionmentioning
confidence: 99%